2011
DOI: 10.1080/00140139.2011.595830
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work characteristics, need for recovery and musculoskeletal problems predict psychological distress in a sample of British workers

Abstract: 2From an original sample of 2454 participants free of self-reported psychological distress, 1463 workers completed a 15-month follow-up. Baseline measures included exposure to job demands, decision latitude, social support and need for recovery. Psychological distress was assessed using the General Health Questionnaire at baseline and at follow up. The findings showed that medium and high exposure to job demands and social support increased the risk of reporting psychological distress at 15-months (RR = 1.65 &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
1
12
0
9
Order By: Relevance
“…Geurts and Sonnentag (2006) argued that states of impaired recovery mediate between job stressors and more chronic health problems. Indeed, a recent longitudinal study identified need for recovery from work as the strongest predictor for muscoskeletal distress (Devereux, Rydstedt, & Cropley, 2011). Our fourth hypothesis reflects this process perspective on job strain as progressing from short-term states of impaired recovery to more chronic and somatic symptoms.…”
Section: H2: Learning Demands Are Positively Related To Intrinsic Motmentioning
confidence: 84%
“…Geurts and Sonnentag (2006) argued that states of impaired recovery mediate between job stressors and more chronic health problems. Indeed, a recent longitudinal study identified need for recovery from work as the strongest predictor for muscoskeletal distress (Devereux, Rydstedt, & Cropley, 2011). Our fourth hypothesis reflects this process perspective on job strain as progressing from short-term states of impaired recovery to more chronic and somatic symptoms.…”
Section: H2: Learning Demands Are Positively Related To Intrinsic Motmentioning
confidence: 84%
“…If repeated insufficient recovery occurs, it may lead to the development of psychosomatic health problems, sickness absence and voluntary turnover (i.e. deliberately deciding to leave the job) in the long term (Sluiter 1999;Devereux, Rydstedt, and Cropley 2011). Need for recovery thus may be seen as an early sign, an entry point to prevent prolonged fatigue (Jansen, Kant, and Van Den Brandt 2002;Kiss et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…For this reason, they provide little direction on how ideas from other prominent models of occupational stress can improve the predictive validity of its multiplicative hypothesis. Preston (2018) and others (Devereux, Rydstedt, & Cropley, 2011;Sonnentag & Zijlstra, 2006) note that one explanation for high-control jobs' strain-buffering and low-control jobs' strain-inducing effect overlooked by most DC research studies, but consistent with the model's theoretical origins, is Karasek's (1998) little-used at-work respite argument. Karasek and Theorell (1990) state that "all living organisms must return their control systems to the rest state… periodically in order to be capable of undertaking the next round of… tasks" (p. 88) and that job control allows employees "to take short periods of relaxation at self-determined… times, even if the job situation is one of intense overall activity and challenge" (p. 94).…”
Section: Modelmentioning
confidence: 90%
“…For this reason, they provide little direction on how ideas from other prominent models of occupational stress can improve the predictive validity of its multiplicative hypothesis. Preston () and others (Devereux, Rydstedt, & Cropley, ; Sonnentag & Zijlstra, ) note that one explanation for high‐control jobs' strain‐buffering and low‐control jobs' strain‐inducing effect overlooked by most DC research studies, but consistent with the model's theoretical origins, is Karasek's () little‐used at‐work respite argument.…”
Section: Introductionmentioning
confidence: 95%